2001
DOI: 10.1159/000052987
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Plasma Endothelin 1 Levels and T Helper 1: T Helper 2 Cell Immunity in Women with Preeclampsia

Abstract: The aim of this study was to investigate the relationship between plasma endothelin 1 (ET-1) levels and T helper (Th)-1:Th2 cell immunity in women with preeclampsia. The percentage of Th1 and Th2 cells and the Th1:Th2 cell ratios in peripheral blood from 11 normal pregnant women and 11 patients with preeclampsia at 29–34 weeks of gestation were calculated using flow cytometry. The plasma ET-1 level was also determined using a modified radioimmunoassay. The plasma ET-1 concentrations and the Th1:Th2 cell ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Epidemiological studies suggest that the maladaption of maternal tolerance is present in pre‐eclamptic cases [2–6]. We and other groups have reported that T helper 1 (Th1)‐type immunity, which induces rejection, is predominant in pre‐eclampsia, supporting this hypothesis [25–31]. Recent studies have demonstrated that CD4 + CD25 bright T cells play a central role in the induction and maintenance of tolerance [32], and CD4 + CD25 + T reg cells are essential for the maintenance of allogeneic pregnancy in mice [11,13].…”
Section: Discussionmentioning
confidence: 93%
“…Epidemiological studies suggest that the maladaption of maternal tolerance is present in pre‐eclamptic cases [2–6]. We and other groups have reported that T helper 1 (Th1)‐type immunity, which induces rejection, is predominant in pre‐eclampsia, supporting this hypothesis [25–31]. Recent studies have demonstrated that CD4 + CD25 bright T cells play a central role in the induction and maintenance of tolerance [32], and CD4 + CD25 + T reg cells are essential for the maintenance of allogeneic pregnancy in mice [11,13].…”
Section: Discussionmentioning
confidence: 93%
“…Pre‐eclampsia is characterized by an abnormal activation of the innate and adaptive immune system 5–10 . Recent data demonstrate that up‐regulation of Th1 responses occurs not only in peripheral blood but also at the feto‐maternal interface in pre‐eclamptic patients 11–18 . It is still unclear if this augmented Th1 response is originated by a defective Treg activity, as suggested for spontaneous abortion 4 …”
Section: Introductionmentioning
confidence: 99%
“…11 The investigations performed during pregnancy complicated with preeclampsia indicated that disturbances of cytokine Th1/Th2 balance are associated with elevated endothelin-1 levels followed by the presence of hypertension. 23 None of the aforementioned studies refered to the autocrine pattern of Th1/Th2 cytokine balance inside maternal decidua in pre-eclampsia and transient hypertension, and their potential role in understanding the local regulatory mechanisms seen in those two syndromes. To clarify this subject, we have focused our attention on comparison between spontaneous and mitogen-stimulated production of IL-2, IL-4, IL-6, IL-10, IL-12 and IFNg in cultured lymhocytes isolated from third trimester decidua of healthy pregnant women, pre-eclamptics and those pregnant with transient hypertension.…”
Section: Introductionmentioning
confidence: 99%